Emotional Working Memory and Alzheimer's Disease. (4th February 2014) - Mammarella, Nicola; Fairfield, Beth
Abstract : A number of recent studies have reported that working memory does not seem to show typical age-related deficits in healthy older adults when emotional information is involved. Differently, studies about the short-term ability to encode and actively manipulate emotional information in dementia of Alzheimer's type are few and have yielded mixed results. Here, we review behavioural and neuroimaging evidence that points to a complex interaction between emotion modulation and working memory in Alzheimer's. In fact, depending on the function involved, patients may or may not show an emotional benefit in their working memory performance. In addition, this benefit is not always clearly biased (e.g., towards negative or positive information). We interpret this complex pattern of results as a consequence of the interaction between multiple factors including the severity of Alzheimer's disease, the nature of affective stimuli, and type of working memory task.